Fertility-Sparing Management of Early Stage Endometrial Cancer: A Narrative Review of the Literature - Alison Montgomery; Marilyn Boo; Jayanta Chatterjee (IMR Press, 2023)
Objectives: The incidence of endometrial cancer (EC) is rising largely due to the increasing levels of obesity along with an ageing population. This has led to an increase in the incidence of premenopausal women with EC. 5% of cases are in patients less than 40 years old, 70% of which are nulliparous at diagnosis. Therefore, fertility considerations must be taken into account when managing these patients. The objectives of this review are to present the fertility-sparing management options available. Mechanism: A detailed computerized literature search of PubMed and MEDLINE up to 1st June 2022 was carried out in order to survey the evidence for fertility-sparing treatment. Studies including patients with endometrial hyperplasia and early-stage EC undergoing fertility-sparing management were included. Findings in Brief: Progestin acts by downregulating oestrogen receptors, thereby suppressing endometrial growth. Oral progestins and the levonorgestrel-releasing intrauterine system (IUS) have therefore been used as non-surgical hormonal treatment for EC. Megestrol acetate (MA) has been shown to produce the highest remission rates compared to other progestins in a systematic review and meta-analysis, but medroxyprogesterone acetate exhibited lower recurrence rates. The IUS for atypical hyperplasia (AH) and EC showed that the majority of patients responded by 3 months' use. A minimum duration of hormonal treatment for AH and EC of 6 months has been advocated, based on randomised studies showing greater efficacy when compared to 3 months treatment. A meta-analysis and systematic review assessing the efficacy of both oral and intra-uterine progestins showed a higher pooled complete response (CR) than with IUS alone. Metformin, gonadotrophin-releasing hormone agonists and weight loss have also been added to progestin regimes with variable results on EC regression. Hysteroscopic resection allows for targeted excision of early-stage EC, but with the risk of perforation and so this has not been recommended by the British Gynaecological Cancer Society or the European Society of Gynaecological Oncology. Assisted reproduction treatment (ART) may be the quickest way to achieve pregnancy once CR is achieved. Pregnancy rates have varied from 32-100%, with live birth rates varying from 17.9-43.8%. Conclusions: EC incidence is on the increase in the premenopausal population along with obesity rates and the average first age of parenthood. Fertility-sparing management of EC should be considered for women where fertility is desired.